2018
DOI: 10.1038/s41467-018-04263-z
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopic compounds in spider aggregate glue remove interfacial water to maintain adhesion in humid conditions

Abstract: Adhesion in humid environments is fundamentally challenging because of the presence of interfacial bound water. Spiders often hunt in wet habitats and overcome this challenge using sticky aggregate glue droplets whose adhesion is resistant to interfacial failure under humid conditions. The mechanism by which spider aggregate glue avoids interfacial failure in humid environments is still unknown. Here, we investigate the mechanism of aggregate glue adhesion by using interface-sensitive spectroscopy in conjuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 52 publications
1
76
0
Order By: Relevance
“…Glycosylations are responsible for the adhesive qualities of spider glue (Singla et al, 2018), and at least 80% of threonine residues in Argiope glues are likely O-glycosylated with mainly N-acetylgalactosamine (GalNAc) (Dreesbach et al, 1983;Tillinghast et al, 1993). The threonine residues are also flanked by glycine and proline, which is consistent with studies that show there is an increase in these residues around O-linked glycosylated threonines (Christlet and Veluraja, 2001;Yoshida et al, 1997).…”
Section: Cobweb Gp G P P Gpg Tpg Vt Gpdg P G Ttpgs Gp G P Pag Gttpg Tsupporting
confidence: 84%
See 1 more Smart Citation
“…Glycosylations are responsible for the adhesive qualities of spider glue (Singla et al, 2018), and at least 80% of threonine residues in Argiope glues are likely O-glycosylated with mainly N-acetylgalactosamine (GalNAc) (Dreesbach et al, 1983;Tillinghast et al, 1993). The threonine residues are also flanked by glycine and proline, which is consistent with studies that show there is an increase in these residues around O-linked glycosylated threonines (Christlet and Veluraja, 2001;Yoshida et al, 1997).…”
Section: Cobweb Gp G P P Gpg Tpg Vt Gpdg P G Ttpgs Gp G P Pag Gttpg Tsupporting
confidence: 84%
“…Spider glue droplets exhibit 1) adhesion, typically to insect prey, 2) extensibility, to remain in contact with struggling prey, and 3) elasticity, to retain prey after extension. Glycosylations have been attributed to glue adhesion (Singla et al, 2018), however potential mechanisms for extensibility and elasticity have only been described for other silks. Orb web weaver glue droplets are more extensible (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Gao et al demonstrated a photodetachable adhesion principle to achieve strong adhesion and easy on-demand detachment for various materials. [29,30] As shown in Figure 1b, the gels presented a robust tensile strength of 47 kPa and toughness of 300 kJ m −3 at the high stain of 1520%. [17][18][19] However, most works only focused on the adhesion behavior in air and/or water, the technology of strong adhesion and acrylate adenine were utilized to fabricate adhesive gels via the radical polymerization in the mixed solvents of water and DMSO.…”
Section: Introductionmentioning
confidence: 87%
“…2019,29, 1900450 Diethyl ether (AR, 96%) and other organic solvents were purchased from Tianjin Tiantai Chemical Works Company.…”
mentioning
confidence: 99%
“…The LMMCs serve several important functions. Along with glycoproteins, they confer hygroscopicity, causing the droplets' size and performance to change over the course of a day as they track environmental humidity (Figure d; Jain et al, ; Opell, Clouse, & Andrews, ; Opell, Jain, et al, ), they maintain glycoprotein structure and solvate glycoprotein, enhancing its surface interaction (Sahni et al, ), and they remove interfacial water from a droplet's contact footprint, enhancing adhesion (Singla, Amarpuri, Dhopatkar, Blackledge, & Dhinojwala, ). Optimal adhesion of an araneoid glue droplet is achieved when the viscosity of the droplet's glycoprotein is low enough to spread on a surface to establish sufficient adhesive contact, but high enough to ensure that the glycoprotein will cohere as it extends, thereby transferring adhesive force to the thread's axial lines (Figure c; Amarpuri, Zhang, Blackledge, & Dhinojwala, ; Amarpuri, Zhang, et al, ).…”
Section: Introductionmentioning
confidence: 99%